Предмет: Алгебра,
автор: ereminaalesia
упростите выражение (a^2-b^2)(2a+b)-ab(a+b)
Ответы
Автор ответа:
0
(a-b)*(a+b)*(2a+b)-ab*(a+b)
Дальше мы (a-b) умножаем на (2a+b):
(2а^2+ab-2аb-b^2)*(a+b)-ab* *(a+b)=(2a^2-ab-b^2-ab)*(a+b)=
=(2a^2-2ab-b^2)*(a+b)= =2a^3-3ab^2-b^3
Ответ: 2a^3-3ab^2-b^3.
Дальше мы (a-b) умножаем на (2a+b):
(2а^2+ab-2аb-b^2)*(a+b)-ab* *(a+b)=(2a^2-ab-b^2-ab)*(a+b)=
=(2a^2-2ab-b^2)*(a+b)= =2a^3-3ab^2-b^3
Ответ: 2a^3-3ab^2-b^3.
Похожие вопросы
Предмет: Геометрия,
автор: prostonnikita
Предмет: Геометрия,
автор: zaremasarsenkul
Предмет: Литература,
автор: nssn8
Предмет: Математика,
автор: Roksi19
Предмет: Обществознание,
автор: ljonjj